Time perspective as a predictor of massive multiplayer online role-playing game playing - Lukavska, Katerina (Cyberpsychology, behavior and social networking, 2012)
This article focuses on the relationship between the time perspective (TP) personality trait and massive multiplayer online role-playing game (MMORPG) playing. We investigate the question of frequency of playing. The TP was measured with Zimbardo's TP Inventory (ZTPI), which includes five factors-past negative, past positive, present hedonistic, present fatalistic, and future. The study used data from 154 MMORPG players. We demonstrated that TP partially explained differences within a group of players with respect to the frequency of playing. Significant positive correlations were found between present factors and the amount of time spent playing MMORPGs, and significant negative correlation was found between the future factor and the time spent playing MMORPGs. Our study also revealed the influence of future-present balance on playing time. Players who scored lower in future-present balance variables (their present score was relatively high compared with their future score) reported higher values in playing time. In contrast to referential studies on TP and drug abuse and gambling, present fatalistic TP was demonstrated to be a stronger predictor of extensive playing than present hedonistic TP, which opened the question of motivation for playing. The advantage of our study compared with other personality-based studies lies in the fact that TP is a stable but malleable personality trait with a direct link to playing behavior. Therefore, TP is a promising conceptual resource for excessive playing therapy.
Keywords: Male; Time Factors; psychologické testy; časové faktory; Humans; osobnost; Psychological Tests; mužské pohlaví; Female; hraní rolí; mladiství; Personality; ženské pohlaví; vnímání času; mladý dospělý; Adult; videohry; Young Adult; Role Playing; Adolescent; Time Perception; dospělí; dítě; lidé; Video Games; Child